The Effect Of Servant Leadership, Compensation, Motivation, And Professional Development On Performance Among Private Vocational High School Teachers - Sudiarti, Nani; Sinlae, Fried (International Journal of Advanced Multidisciplinary, 2023)
This study aims to examine the effect of servant leadership, compensation, motivation, and professional development on performance among teachers in private vocational high schools. The research method used was a survey by distributing questionnaires to teachers in some private vocational high schools in various regions. The results of the study indicate that servant leadership has a positive and significant effect on performance. Compensation also contributes positively to teacher performance, demonstrating that financial rewards can motivate them. Teacher motivation also has a positive effect on teacher performance. Furthermore, teacher professional development has a positive impact on performance, highlighting the importance of investments in improving teacher qualifications and skills. The findings of this study offer valuable insights for the management of private vocational high schools in enhancing teacher performance through the implementation of servant leadership, improving compensation, increasing motivation, and enhancing professional development. This step can help create a more effective learning environment and positively impact the quality of education in private vocational high schools.